Goat farming in Algerian steppe region: constraints and perspectives - Mouhous A.; Guermah H.; Kadi S.A.; Djellal F. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
This study aims to characterize the goat farming in steppe zone at M’sila region (Algeria) and to identify its main constraints. In Algeria, goats are distributed mainly in the mountains, the steppe and Saharan areas. The goat population in this agro-pastoral region is about 140000 goats of which 90000 females. A survey of 64 breeders confirmed extensive and mixed management with sheep. The price of goat meat has been in line with sheep’s meat, which remains the most consumed meat in the study area. The market demand for goat meat is accentuated especially during the aid Al-Adha and Ramadhan as well as for the farmers’ fresh money requirements. Goats are sold around 30000 Algerian dinars depending on age and weight. Otherwise, the price of goat milk, which is gaining interest, has tripled. Despite the attractive price of the goat milk, 67% of the breeders prefer it for to self-consumption. These farms are almost exclusively conducted by men (97%) of over 55 years old. Better organization of the goat sector could make it more profitable and play an important role in rural development.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)